Immersive journalism and its application in media business - Sánchez Franco, Víctor; Lavilla Muñoz, David José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Immersive journalism is being notorious in mass media little by little. Multimedia platforms are a good place to distribute the new communication trends, The main objectives of this research look forward to demonstrate if the immersive communication can be a good proposal for the prosumer. To achieve these objectives, a qualitative method is going to be used, based on interviews with experts. The conclusions offer a close view of the current situation of the framework about immersive journalism around the world.